(untitled) - Richardson, Donald V. (Upper Saddle River, New Jersey, 1996)
This book offers the knowledge about the various existing types of electric motors and generators. It includes semiconductor control devices and triggering of elctronic controls, basic transferrable switches, integration of TSWs and their triggering circuits, SI unit relationships with conversion tables to English units, efficiency undrstanding and measurement, machine frame sizes and intasllation dimensions and ratings
Keywords: Electric machinery,Electric transformers